2009
DOI: 10.1039/b815121k
|View full text |Cite
|
Sign up to set email alerts
|

The metathesis of α-olefins over supported Re-catalysts in supercritical CO2

Abstract: At 35 • C, in the presence of supercritical carbon dioxide (80-150 bar) as a solvent, a-olefins (RCH=CH 2 , R = C4-C6) undergo highly selective self-metathesis catalyzed by supported Re-oxide (7%). To the best of our knowledge, this is the first procedure for the metathesis of alkenes, in which heterogeneous catalysts are combined with the use of dense CO 2 . The intrinsic eco-compatibility and the unique physicochemical properties of this medium offer both environmental and synthetic advantages: not only conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…This product distribution matched our previous findings for the same reaction carried out under batch-CO 2 systems. 7,10 Although preliminary, these results proved that unprecedented reaction conditions obtained by the combination of a CF-scCO 2 reactor with Al 2 O 3 -supported Re 2 O 7 catalysts, were suitable for metathesis processes.…”
Section: The Apparatus For Continuous-flow Metathesis Reactionsmentioning
confidence: 77%
See 2 more Smart Citations
“…This product distribution matched our previous findings for the same reaction carried out under batch-CO 2 systems. 7,10 Although preliminary, these results proved that unprecedented reaction conditions obtained by the combination of a CF-scCO 2 reactor with Al 2 O 3 -supported Re 2 O 7 catalysts, were suitable for metathesis processes.…”
Section: The Apparatus For Continuous-flow Metathesis Reactionsmentioning
confidence: 77%
“…At 35°C and 90 bar, the maximum CF-conversion for the selfmetathesis of 1-octene (23%) is far lower than that (65-70%) obtained for the same reaction in the static mode. 7,10 Also, a CO 2 pressure dependence is observed for the CF-metathesis, while the corresponding batch process is insensitive to pressure effects. The reaction environment is therefore greatly differentiated when CF-dynamic or static conditions are used.…”
Section: Continuous-flow Vs Batch Conditions For Metathesis Reactions In Sccomentioning
confidence: 98%
See 1 more Smart Citation
“…(Scheme 3) [10,28,29]. In a previous paper [30] we have observed that alumina is the best support for Re-oxide for the metathesis of 1-octene in scCO 2 . Under these conditions, the most significant aspect was that scCO 2 could not only act as a solvent for the reaction, but it also improved the overall efficiency (Table 2) [30].…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…In a previous paper [30] we have observed that alumina is the best support for Re-oxide for the metathesis of 1-octene in scCO 2 . Under these conditions, the most significant aspect was that scCO 2 could not only act as a solvent for the reaction, but it also improved the overall efficiency (Table 2) [30]. At 35°C, the reaction proceeded with an average conversion of over 30% higher in the supercritical medium than in classical liquid solvents such as n-heptane or toluene.…”
Section: Catalyst Preparationmentioning
confidence: 99%